Analysis of Work Implementation Related to the Quality Management System on the Light Rail Transit (LRT) Phase 1B Project - Redwan, Muhammad; Isradi, Muhammad (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study analyses the Implementation of the quality management system in the Light Rail Transit (LRT) Phase 1B project work on the Veledrome-Manggarai route spanning 6.4 km. The research employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) and Customer Satisfaction Index (CSI) methods to analyze factors affecting quality management system implementation across four main work phases: borepile, pilecap, pier, and pierhead. Data were collected through structured questionnaires from 70 respondents comprising owners, contractors, and supervisory consultants. Results indicate that borepile work has the highest R² value (0.477), with material variables as the most dominant factor (path coefficient 0.294). The Fc 35Mpa concrete material indicator contributes most significantly (29%) to the quality management system. CSI analysis shows the highest stakeholder satisfaction level in pierhead work (90.88%) and lowest in pier work (79.78%). This research contributes to identifying critical factors in quality management systems for mass transportation infrastructure projects and provides a framework for quality performance evaluation in similar projects.